PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN MINAT BELAJAR SISWAPADA MATA PELAJARANSKIKELAS IV DI MI HUBBUL WATHAN PETAI KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Grasela Via Lorensa; Sopiatun Nahwiyah; Helby Akbar (Universitas Islam Kuantan Singingi, 2021)
Education is tuition which is passed to by a somebody to reach specific-purpose science target that is add science, forming x'self character, and instruct somebody to become better person in activity learn, Permasalahn from this Research early from lowering enthusiasm nya learn class IV student in MI Hubbul wathan petai. This matter is the background overshadow researcher to conduct research by using study Discovery Learning model, model study Discovery Learning represent a[n study model developed [by] pursuant to view kontruktisme. Model this emphasize at understanding to concept in pembelajran [of] through student involvement actively in course of study. Intention of this research is to know enthusiasm learn siswa,serta constraints faced by student at the (time) of study. type of Research used by Research of Class Action ( PTK) with descriptive method qualitative subjek of this research is student of class of IV MI Hubbul wathan petai with amount 22 student people, technique of data collecting used by observation, wawancar,.dan documentation. Result of research of menunjukan that study by using model of study of Discovery Learning can improve enthusiasm learn student, this matter [is] proven from result of perception obtained by each;every its cycle, at Pre of cycle of presentase of enthusiasm learn student only reach 34.54%, at cycle of I mount to become 63,63% and [at] cycle of II go up to become 94,09%, hence earn disimpukan that applying model study of Discovery Learning executed in study of SKI of items missionize prophet of muhammad SAW can improve enthusiasm learn student of class of IV MI.